Avoiding caesarean section in maternal hypothermia associated with marked fetal distress. Issue 3 (25th February 2008) - Usman, S Bose; Menon, V
Abstract : A 37-weeks pregnant woman was admitted to the accident and emergency department with hypothermia following possible drug misuse. Although her pulse and blood pressure were normal, her fetus was found to have marked bradycardia. This caused anxiety and quick transfer of the unconscious and still hypothermic woman to the maternity unit. The baby was, however, not immediately delivered by caesarean section. Instead, rewarming of the mother was undertaken, which produced a rise in fetal heart rate as the maternal temperature rose. A healthy baby was eventually born after spontaneous labour. This report discusses the effects of hypothermia on the body and fetus. It also discusses the rationale for delaying delivery of baby until hypothermia is corrected.